Low Enthalpy Geothermal Systems in Structural Controlled Areas: A Sustainability Analysis of Geothermal Resource for Heating Plant (The Mondragone Case in Southern Appennines, Italy) - Marina Iorio (Energies, 2020)
In this study, the sustainability of low-temperature geothermal field exploitation in a carbonate reservoir near Mondragone (CE), Southern Italy, is analyzed. The Mondragone geothermal field has been extensively studied through the research project VIGOR (Valutazione del potenzIale Geotermico delle RegiOni della convergenza). From seismic, geo-electric, hydro-chemical and groundwater data, obtained through the experimental campaigns carried out, physiochemical features of the aquifers and characteristics of the reservoir have been determined. Within this project, a well-doublet open-loop district heating plant has been designed to feed two public schools in Mondragone town. The sustainability of this geothermal application is analyzed in this study. A new exploration well (about 300 m deep) is considered to obtain further stratigraphic and structural information about the reservoir. Using the derived hydrogeological model of the area, a numerical analysis of geothermal exploitation was carried out to assess the thermal perturbation of the reservoir and the sustainability of its exploitation. The effect of extraction and reinjection of fluids on the reservoir was evaluated for 60 years of the plant activity. The results are fundamental to develop a sustainable geothermal heat plant and represent a real case study for the exploitation of similar carbonate reservoir geothermal resources.